EVALUASI EFEKTIVITAS PELAKSANAAN ONLINE GROUP DISCUSSION (OGD) UNTUK PENGEMBANGAN KOMPETENSI SDM DI BMKG PADA SAAT PANDEMI COVID-19 - Tarmana, Dede; Kasmanto, Rony (Jurnal Widya Climago, 2021)
Pandemic Covid-19 has occuure and spread to all the world in periode while more one year. It’s impact to some live sectors, include sector of human resources competence development. Majority of human resources competence development programe changing from classical to virtual. In Agency of meteorology, climatology and geophysics, one of some method for human resources competence development conduct by Center for training & education is online group discussion (OGD). But how far effectivity of this programe isn’t knew yet. So the goal of this study is to know effectivity of conline group discussion enforcement. Data generated from respondent that answer some question in evaluation instrument on level reaction Kirkpatrick evaluation method. Reaseach methode has used such as survey for data collect, statistic descriptive, snowball graph visualization, and classification of effectivity level. Result of this study show that effectivity from 5(five) variables, that is material content, capability of presenter, capacity of moderator to manage discussion, organizing committee, and infrastructure supporting, all of variables get assessment value in average 4.7, Its mean eoforcement of OGD is very effective. Base on calculate result for respondent proportion, shown that majority of respondent (almost >90%) from 323 respondent agree with effectivity category for OGD enforecement is very an effective. Keywrods : Pandemic Covid-19, Online Group Discussion, virtual, human resources.